A Samaan Tree, Trinidad - (:unkn) unknown (My University, 2010)
A cow grazes near a Samaan Tree located in an open field. This postcard is addressed to Miss Marion Clarke, Massachusetts and affixed is a 3 cents Trinidad and Tobago postage stamp.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Savannas--Trinidad and Tobago; Cattle--Trinidad and Tobago; Parks--Trinidad and Tobago; [1954]; Shade trees--Trinidad and Tobago